2021
DOI: 10.1051/shsconf/20219206017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility on business competitiveness

Abstract: Research background: The social and environmental problems of the current globalised world are primarily targeted on the South and Southeast Asian business environment. However, according to the idea “think global, act local”, practices of Czech local business also contribute to the global environment. Purpose of the article: The Czech Republic is classified as a small open economy in the final stage of a transformation into a market economy, and on the top of that, it is also a member of the European Union. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At the same time, due to the lack of statistically reliable information on sick-leave certificate payments for employees with disabilities, they were taken in 1.5-3 times more than accidental payments for employees without disabilities, depending on working conditions. The implementation of corporate social responsibility practices in the development of business processes shows that positive changes, both long-term and shortterm, are observed in most cases, but it is difficult to evaluate them numerically [16][17][18][19]. In this regard, the assessment of the role of corporate social responsibility was determined based on the data that consumers of products who are aware of the company's desire to carry on their business in accordance with social responsibility choose this particular product or service, which is estimated by an increase in sales revenue by 2.8 % [19].…”
Section: Presentation Of the Basic Materialsmentioning
confidence: 99%
“…At the same time, due to the lack of statistically reliable information on sick-leave certificate payments for employees with disabilities, they were taken in 1.5-3 times more than accidental payments for employees without disabilities, depending on working conditions. The implementation of corporate social responsibility practices in the development of business processes shows that positive changes, both long-term and shortterm, are observed in most cases, but it is difficult to evaluate them numerically [16][17][18][19]. In this regard, the assessment of the role of corporate social responsibility was determined based on the data that consumers of products who are aware of the company's desire to carry on their business in accordance with social responsibility choose this particular product or service, which is estimated by an increase in sales revenue by 2.8 % [19].…”
Section: Presentation Of the Basic Materialsmentioning
confidence: 99%
“…A study by Kožená and Mlázovský (2021) found that most Czech companies do not consider CSR as a critical factor for their competitiveness. The results of our study show that Czech consumers make distinctions in their purchasing decisions, albeit more implicitly, which may be necessary for determining CSR strategies.…”
mentioning
confidence: 99%